Microbial functional attributes, rather than taxonomic attributes, drive top soil respiration, nitrification and denitrification processes - Chen, Qing-Lin; Ding, Jing; Li, Chao-Yu; Yan, Zhen-Zhen; He, Ji-Zheng; Hu, Hang-Wei (The Science of the total environment, 2020)
We lack empirical evidence for the relative importance of microbial functional attributes vs taxonomic attributes in regulating specified soil processes related to carbon (C) and nitrogen (N) cycling, which has hindered our ability to predict the responses of ecosystem multifunctionality to environmental changes. Here, we collected soil samples from a long-term experimental field with eight inorganic and organic fertilization treatments and evaluated the linkage between microbial functional attributes (abundance of functional genes), taxonomic attributes (microbial taxonomic composition), and soil processes including soil respiration, denitrification and nitrification. Long-term fertilization had no significant effect on the bacterial or fungal alpha-diversity. The treatments of chicken manure and sewage sludge addition significantly altered the rates of soil respiration, denitrification and nitrification, which were significantly correlated with the abundances of relevant functional genes. Random forest model indicated that the abundance of functional genes was the main diver for the rate of soil processes. The predominant effect of microbial functional attributes in driving soil processes was maintained when simultaneously accounting for multiple abiotic (total C, total N and soil pH) and biotic drivers (bacterial and fungal community structure), indicating that microbial functional attributes were the predominant driver predicting the rate of soil respiration, denitrification and nitrification. Our results suggested the importance of developing a functional gene-centric framework to incorporate microbial communities into biogeochemical models, which may provide new insights into the biodiversity-functions relationship and have implications for future management of the consequences of biodiversity loss for ecosystem multifunctionality. [Display omitted] •The QMEC is a powerful approach to analyze a wide spectrum of functional genes.•Organic fertilization increased the rate of soil respiration, nitrification and denitrification.•Microbial functional attributes are more sensitive predictors of soil C and N cycling.